Oral History Program Interview: Martha Lee Martin Jackson - Jackson, Martha Lee Martin
Jackson was born in Lenna, Oklahoma on July 13, 1922. She and her family came to Bakersfield, California in October of 1937 and continued to Fresno. This interview includes subjects regarding rejudice towards "Okies" at schools and in general, New Deal relief policies, how people responded to the Dust Storms, her reasons for ditch camps, women working in fields and canneries, prejudice towards racial minorities, and how The Grapes of Wrath is an embarrassing and untrue characterization of "Okies."